A Review of Human Exposure to Microplastics and Insights Into Microplastics as Obesogens - Kannan, Kurunthachalam; Vimalkumar, Krishnamoorthi (Frontiers in Endocrinology, 2021)
The ubiquitous exposure of humans to microplastics (MPs) through inhalation of particles in air and ingestion in dust, water, and diet is well established. Humans are estimated to ingest tens of thousands to millions of MP particles annually, or on the order of several milligrams daily. Available information suggests that inhalation of indoor air and ingestion of drinking water bottled in plastic are the major sources of MP exposure. Little is known on the occurrence of MPs in human diet. Evidence is accumulating that feeding bottles and medical devices can contribute to MP exposure in newborns and infants. Biomonitoring studies of human stool, fetus, and placenta provide direct evidence of MP exposure in infants and children. MPs <20 µm were reported to cross biological membranes. Although plastics were once perceived as inert materials, MP exposure in laboratory animals is linked to various forms of inflammation, immunological response, endocrine disruption, alteration of lipid and energy metabolism, and other disorders. Whereas exposure to MPs itself is a concern, MPs can also be sources of exposure to plastic additives and other toxicants. Exposure of human cell lines to MP additives such as phthalates, bisphenols, and organotins causes adverse effects through the activation of nuclear receptors, peroxisome proliferator-activated receptors (PPARs) α, β, and γ, and retinoid X receptor (RXR), leading to oxidative stress, cytotoxicity, immunotoxicity, thyroid hormone disruption, and altered adipogenesis and energy production. The size, shape, chemical composition, surface charge, and hydrophobicity of MPs influence their toxicity. Maternal transfer of MPs to the developing fetus has been demonstrated in exposed laboratory animals and through the analysis of human placenta. In laboratory animal studies, maternal exposure to MPs altered energy and lipid metabolism in offspring and subsequent generations. Moreover, concomitant with the global increase in plastics production, the prevalence of overweight and obesity in human populations has increased over the past five decades, and there is evidence to support the hypothesis that MPs and their additives are potential obesogens. Even though MP exposures are ubiquitous and toxic effects from such exposures are a concern, systematic studies on this topic remain urgently needed.